Territórios e territorialidades em praças de Aracaju/SE - Santos, Emanuela Carla (2016)
The squares are part of the layout of the western cities since Ancient Age, serving different uses, being versatile and relevant environments of the urban context. In Aracaju it is possible to observe how the squares constitute a rich space for the urban environment, showing a wide network of relations of its inhabitants with each other and the city. Power relations that are established in the markets lead to the formation of territories. In this context, the hypothesis to be defended is that knowledge of territoriality present in the markets constitutes an essential element for more efficient management. The general objective of the research is to analyze the territoriality of the squares, relating them to physical and cultural dimensions. The specific objectives, it has: reveal the territoriality present in Aracaju’s squares; evaluate the location, offer gifts equipment and its use in the squares; see how locals and regulars perform the symbolic appropriation of the squares; analyze how power relations influence the use of Aracaju’s squares. To achieve the stated objectives, the study was implemented in eight squares of Sergipe's capital. The research consisted of a literature review about the concepts of space, territory and territoriality, data collection in the field and crossing information obtained to indicate the existing territories. To see how the territoriality are made, we used the qualitative and quantitative evaluation matrix to the squares and interviews with surrounding residents and frequenters of the analyzed markets. The relationship between materiality and social actors are present in all the squares, in many different ways. The size of the territory that prevails in Aracaju’s squares is cultural, with the symbolic appropriation at different times of the day. The territories formed in the eight squares chosen for this study were classified into seven types: territory accessibility, territories of physical activity, trade territories, territories of children's club, territories of events, religious territories and topofobics territories. It follows, therefore, that analyze how territorialities constitute becomes an important management tool, enabling you to evaluate how passers make use of the square, making them sharers for better management and use of this important category of area recreation.